PEMANFAATAN EKSTRAK KAYU MERBAU UNTUK PEREKAT PRODUK LAMINASI BAMBU - Adi Santoso; I.M. Sulastiningsih; Gustan Pari; Jasni (Jurnal Penelitian Hasil Hutan, 2016)
The report describes the useof adhesive made frommerbau wood extract (Intsia Spp.) which is allowed tocopolymerize with resorcinol, formaldehyde under alkaline conditions, and tapioca as an extender. The adhesive was used to manufacture three-ply composite board consisting of a back and core layers made from sengon (Falcataria mollucana), and jabon (Anthocephalus chinensis), while the face layer was made either one of three bamboo species, namely, andong (Gigantochloa pseudoarundinacea), mayan (Gigantochloa robusta Kurz.), and bitung (Dendrocalamusasper Schult. F.). Result shows that physical-mechanical properties of the composite board with using adhesive by formula (% of weightratio) Merbau extract :Resorcinol 50%: Formaldehyde 37%:Extender=100 : 10 : 10 : 5) were similar with to those of products made of synthetic phenolic adhesive and classified as an exterior quality type with E or 0 F**** typesof low formaldehyde emission.